Acupuncture for the treatment of trigeminal neuralgia: A protocol for the systematic review of randomized controlled trials. Issue 11 (March 2018) - Kim, Jong-In; Kim, Hee-Jung; Lee, Jung Ju; Jun, Ji Hee; Choi, Tae-Young; Lee, Myeong Soo
Abstract: Background: The ability of acupuncture to successfully control pain has been reported in the past. However, currently no systematic reviews exist regarding the effect of acupuncture on trigeminal neuralgia (TN). This proposed review aims to evaluate the current evidence on the efficacy of acupuncture for the management of pain in TN. Methods: A total of 11 databases were searched from their inception. These include MEDLINE, AMED, EMBASE, the Cochrane Library, 6 Korean medical databases, and 1 Chinese Medical Database. Study selection, data extraction, and assessment were performed independently by 2 researchers. Risk of bias was assessed via the Cochrane risk of bias assessment tool. Ethics and dissemination: Ethical approval is not required, given that this protocol is for a systematic review. The systematic review will be published in a peer-reviewed journal and disseminated both electronically and in print. The review was updated to inform and guide healthcare practice and policy. Trial registration number: PROSPERO 2018 CRD42018087594.